The effect of different density towards survival rate of Marble Goby (Oxyeleotris marmorata Blkr.) in closed transportation - Arini, Endang; Elfitasari, Tita; Purnanto, Siwi Hadi (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2011)
Marble Goby is a fresh water fish with high economic value. The marble goby grow-out business require fish seed  from various seedling Centres. To obtain such output require adequate seeds supply from many sources as well as appropriate transportation. The optimum density of Marble Goby seed in closed transportation is not yet known, therefore, a research on this issue is needed to ensure fish seed quality and survival rate.The aim of this study is to observe the effect of different densities on the survival rate of Marble Goby sized 100 g/ind. and to observe the best density during their transportation using 10 hour – closed system. This study applied a  complete random design method with 4 density treatments, which consist of 6 ind./L, 8 ind./L, 10 ind./L, and 12  ind./L. Each treatment was subject to three replications. Data used were survival rate, energy, activity, and water quality. The study found that different density resulted in significant effect (P < 0.01) on the survival of marble goby seeds. Survival rates of each treatment are as follows: (A) 100%, (B) 95.83%, (C) 93.33%, and (D) 80.56%.  Treatment B with density rate of 8 ind/L provided the most reliable density related to the transportation of marble goby using a 10 hour – closed system. Key words: marble goby, transportation, density, survival.